The Antibody Germline/Maturation Hypothesis, Elicitation of Broadly Neutralizing Antibodies Against HIV-1 and Cord Blood IgM Repertoires - Prabakaran, Ponraj; Chen, Weizao; Dimitrov, Dimiter S. (Frontiers in Immunology, 2014)
We have previously observed that all known potent broadly neutralizing antibodies (bnAbs) against HIV-1 are highly divergent from their putative germline predecessors in contrast to bnAbs against viruses causing acute infections such as henipaviruses and SARS CoV, which are much less divergent from their germline counterparts. Consequently, we have hypothesized that germline antibodies may not bind to the HIV-1 envelope glycoprotein (Env) because they are so different compared to the highly somatically mutated HIV-1-specific bnAbs. We have further hypothesized that the immunogenicity of highly conserved epitopes on the HIV-1 envelope glycoproteins (Envs) may be reduced or eliminated by their very weak or absent interactions with germline antibodies and immune responses leading to the elicitation of bnAbs may not be initiated and/or sustained. Even if such responses are initiated, the maturation pathways are so extraordinarily complex that prolonged periods of time may be required for elicitation of bnAbs with defined unique sequences. We provided the initial evidence supporting this antibody germline/maturation hypothesis, which prompted a number of studies to design vaccine immunogens that could bind putative germline predecessors of known bnAbs and to explore complex B cell lineages. However, guiding the immune system through the exceptionally complex antibody maturation pathways to elicit known bnAbs remains a major challenge. Here, we discuss studies exploring the antibody germline/maturation hypothesis as related to elicitation of bnAbs against HIV-1 and present our recent data demonstrating the existence of germline-like precursors of VRC01 antibodies in a human cord blood IgM library.